Há informações stewardship nos relatórios contábeis? - Almeida, Sirlene de Aguiar Fernandes (2020)
The stewardship objective must provide ex post accounting information to assist in the assessment of the use of the capital invested. By doing so, the prominence given to accounting information consistent with the stewardship objective, included in the Conceptual Framework by the IASB in 2018, contributes to greater verifiability and reliability of management actions and decisions made internally by corporate management in the resource allocation. The general objective of present study was to verify the association of the accounting information disclosed in the accounting reports with the stewardship objective. Therefore, accounting reports published by companies with active registration in the Exchange, Brazil, Balcão (B3), from 2018 were analyzed. Considering the representativeness of the population, 97 non-financial companies were analyzed. From the statements mentioned in the review process of the Conceptual Framework for Financial Reporting, it was possible to map the information present in the accounting reports that could help external users to bespeak how effective of the company´s management. This information was segregated into six (6) criteria for empirical disclosure of the stewardship objective: creation of value, use of economic and financial resources, protection against adverse effects, compliance with the laws inherent to the activity, accomplishment with contractual clauses and reliability of accounting information. Through the keywords, a content analysis was performed based on the weighted criteria in 15 operational measures which received a scaled score from (zero) to (five), statistically validated. The result obtained shows that the signaling requirements for compliance with the stewardship objective as an intrinsic objective to the general objective are satisfactory results of validity and reliability. Thus, the results of the study can contribute to a better understanding of the term stewardship, as well as the possibility of meeting the objective of issuing accounting reports established by the IASB. Accordingly, further study is necessary to specify motivational and the control aspects to meet managements goals in accounting reporting clearly and distinct from the utility-decision objective.